Expression of the initiator caspase-8 in the epithelium of physiological ectopy in young women, infected with Human papillomaviruses - Patskov, A. O. (Journal of Education, Health and Sport, 2018)
More and more often clinical cases of severe cervical lesions and cervical cancer are observed against the background of physiological ectopy at a young age. In most of them, Human papillomaviruses (HPVs) are detected at the examination, with severe intraepithelial lesions and initial forms of cancer identifying highly oncogenic strains of HPVs. The purpose of the study was to study the expression of the initiator caspase-8 in the epithelium of physiological ectopy in young women infected with HPVs. Material and methods. A randomized prospective cohort study was conducted on 180 patients aged 18-25 years, of which 150 were with physiological cervical ectopy and 30 without pathological changes in the cervix. The survey included extended colposcopy, HPV-screening, Pap-test, the quantitative determination of the level of human caspase-8 in lysates of cervical epithelial cells. Results. In patients with physiological ectopy of the cervix and the detection of high-oncogenic HPVs there was a low expression of caspase-8 (0.18 ± 0.01 ng/ml), which was less in comparison with the same in patients with physiological ectopy of the cervix and with low-oncogenic HPVs (1.72 ± 0.02 ng / ml) in 9.55 times, in women with physiological ectopy of the cervix and without infection of the HPVs (1.76±0.03 ng/ml) – in 9.78 times, in control group without physiological ectopy of cervical epithelium and without HPVs (1,78±0,04 ng/ml) – in 9,89 times. Conclusions. High-oncogenic HPV is actively involved in blocking apoptosis and reducing the activity of the enzyme initiating caspase-8, which leads to the disregulation of the cellular differentiation cycle, exfoliation, and disturbance of physiological metaplasia in the transformation zone.